Egypt : Economic Monitoring Note, Spring 2013 - World Bank (Washington, DC, 2014)
The political situation in Egypt remains highly volatile and uncertain. The political environment is highly fragmented with increasing polarization between the Muslim brotherhood and other less organized factions that include secular and liberal parties as well as supporters of the former regime. At the same time, confrontations between the authorities and the judiciary continue to resurface. Following the controversial assumption of temporary exceptional powers, the president pushed forward a referendum on the new constitution in December which was approved by a small majority but with a low voter turnout. New Parliamentary elections were called in late February to begin in late April, but the election law was subsequently challenged in the courts. This will likely delay elections until August. Meanwhile, the key opposition parties have declared that they will boycott the elections.